VGLL4 Protects against Oxidized-LDL-Induced Endothelial Cell Dysfunction and Inflammation by Activating Hippo-YAP/TEAD1 Signaling Pathway. (30th December 2020) - Xu, Kaicheng; Zhao, Haomin; Qiu, Xiaolei; Liu, Xiwen; Zhao, Fucheng; Zhao, Yue
Abstract : Vestigial-like 4 (VGLL4) has been found to have multiple functions in tumor development; however, its role in cardiovascular disease is unknown. The aim of this study was to investigate the effect of VGLL4 on the dysfunction and inflammatory response of Ox-LDL-induced human umbilical vein endothelial cells (HUVECs) and its mechanism, so as to provide a new theoretical basis for the diagnosis and treatment of atherosclerosis. In the present study, the protective activity of VGLL4 inhibiting Ox-LDL-induced apoptosis, oxidative stress, inflammation, and injury as well as its molecular mechanisms was examined using human umbilical vein endothelial cells (HUVECs). The results showed that the expression of VGLL4 was decreased with the increase of Ox-LDL concentration in HUVECs. In addition, the functional study found that VGLL4 overexpression alleviated Ox-LDL-induced oxidative stress, inflammation, and dysfunction and inhibited apoptosis. Further research found that VGLL4 regulated Hippo-YAP/TEAD1 signaling pathway, and the Hippo-YAP/TEAD1 signaling pathway was involved in the protective mechanism of VGLL4 on HUVECs. In conclusion, it suggests that VGLL4 protects against oxidized-LDL-induced endothelial cell dysfunction by activating the Hippo-YAP/TEAD1 signaling pathway.